Examining Selected Newspapers’ Framing of the Renewed Biafran Agitation in Nigeria (2016 – 2017) - Ezu, Victor Chinedu (2020)
The renewed Biafran agitation headed by In-digenous People of Biafra (IPOB) has been in the news since 2016. This is surprising when one considers that the Nigerian-Biafran war was fought over 50 years ago with no vic-tor and no vanquished stance. This research examines how selected newspapers framed the Biafran agitation from January, 2016 to December, 2017 – a period which recorded a spike in the activities of Biafran agitators who called for a referendum to carve out the Republic of Biafra. Framing theory is em-ployed as the theoretical frame work for this research. Four hundred and twenty-one (421) issues of selected newspapers were sampled through purposive and critical case sampling techniques. The data were analysed through qualitative and quantitate content analysis. Findings of this research showed that selected newspapers framed the agitation from politi-cal, economic, separatist, human rights, con-flict and hate speech frames. Findings also show that media correspondents were the pri-mary frame source for stories on the renewed Biafran agitation. The print media perceived the agitation mainly from human rights crisis where the agitators are deprived of the free-dom to protest and are dehumanised by the Nigerian security operatives; and questioned the government over human rights abuses.